Trabeculectomy with mitomycin C for glaucoma secondary to emulsified silicone oil after pars plana vitrectomy: three-years follow up - Marjanović Ivan; Gvozdenović Ranko; Božić Marija; Marić Vesna; Stojković Milenko; Marjanović Marija; Jordanova Elena; Martinez Antonio (Vojnosanitetski Pregled)
Background/Aim. Different surgical interventions have been proposed, including trabeculectomy associated with antiproliferative agents because silicone oil (SO) removal cannot necessarily provide intraocular pressure (IOP) control. The aim of the study was to determine the efficacy of trabeculectomy with mitomycin C (MMC) for lowering IOP in patients with open-angle glaucoma (OAG) secondary to emulsified SO after pars plana vitrectomy. Methods. A single-center, prospective study was conducted, from December 2014 to December 2019, on 56 consecutive patients with an uncontrolled elevation of IOP after SO removal who were subjected to trabeculectomy with mitomycin MMC in that period. The primary end-point was the IOP at the three-year follow-up visit. Complete surgical success was defined as an IOP ranging from 7 mmHg to 18 mmHg without glaucoma medication. Qualified success was defined a s I OP ≤ 2 1 m mHg with one or two topical medications. Results. Fifty-six patients with a mean age of 5 3.6 [standard deviation (SD)15.5] years had a mean baseline IOP of 42.3 (39.3 to 45.3) mmHg, which reduced to 18.6 (17.9 to 19.3) mmHg three years after surgery (p < 0.0001). Seventeen (30.4%) eyes were classified as a complete success, 21 (37,5%) as a qualified success, and 18 (32.1%) as a failure. In all successfully treated patients, the number of antiglaucoma medications was significantly reduced from 2.85 (SD 0.77) to 1.63 (SD 0.62), p < 0.0001. Conclusion. Trabeculectomy with MMC may be an option for lowering IOP in patients with OAG secondary to emulsified SO after pars plana vitrectomy, which was not controlled with maximum